Fixed Point Theorem in 2-Normed Spaces - Francis Yunito Rumlawang (Tensor: Pure and Applied Mathematics Journal, 2020)
In this paper we prove a fixed point theorem in a complete 2-normed Spaces. We define a norm derived from 2-norm. To get the theorem proved we first study some convergent and Cauchy sequences, and contractive mappings in 2-normed spaces.